Stress recognition using photoplethysmogram (PPG) signal incorporating gender and age variability - Noor Hafizah Azlin binti Abd Halim (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Stress issue is crucial nowadays as it is not only affecting individual's performance but also their health regardless their age and gender. Currently, there are many research on stress recognition, though, little has been said on detecting stress incorporating gender and age factors. Therefore, this study proposed a novel method of stress recognition using Photoplethysmogram (PPG) signal incorporating gender and age variability. PPG devices are now widely used and chosen because it is convenient, low power, cheap and easy to handle due to its small size. A total of 30 subjects were involved in this study, which consists of 15 females and 15 males with different ages and gender. The PPG signals were taken in resting condition using pulse oximetry called Easy Pulse hardware. The subjects went through Stroop test in order to record the physiological change. The data were collected before and after the test is conducted and will be extracted and categorised using classification techniques to differentiate between normal and stress conditions incorporating different gender and age groups. The scope of this study only considers healthy individuals. For this study, the data were classified using peak differences and Cardiod area differences. For gender groups, the result shows that female have a tendency to be more stressful as their systolic peak and Cardiod area differences are much higher as compared to male. These results are in line with the past research done by Seedat et al. which stated that the lifetime risk of most mood disorders and all anxiety disorders for women are much higher than men. On the other hand, for age factors, the age group of 20-29 years old (Group B) obtained high values as compared to other age groups which can be assumed that they are more stressful than the others. This result is supported by Cavanough et al. which stated that younger adults experience more stress as compared to older adults. While, the people in the age of 40-49 years old (Group D) shows less stress. Based on the overall results obtained, it shows that PPG signal are capable of recognizing stress incorporating gender and age variability.